2020
DOI: 10.1002/joc.6606
|View full text |Cite
|
Sign up to set email alerts
|

Statistical characterization of the sea‐breeze physical mechanisms through in‐situ and satellite observations

Abstract: The physical mechanisms that take place under sea-breeze (SB) conditions in the Palma basin (Mallorca island, western Mediterranean sea) are analysed through the inspection of data from automatic weather stations (AWS) during the period 2009-2017. Satellite-derived land-surface and sea-surface temperatures (LST and SST, respectively) are used to compute the surface temperature difference (LST-SST) in the Palma basin. It is found that during daytime hourly averages for each month of this difference are always p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 62 publications
(105 reference statements)
2
11
0
Order By: Relevance
“…The mean 2-m temperature at 0800 LST is basically 3°C higher in T1 and T5 than in T2. As suggested in Grau et al (2020) based on high-resolution satellite observations, a higher environmental temperature tends to accompany a larger land-sea ΔT, which contributes to the establishment of sea breeze circulation. Here, it is difficult to use the global reanalysis data to directly resolve a realistic value of ΔT between the irrigated and arid areas.…”
Section: Synoptic Pattern Preference Of Boundaries and Their Associat...mentioning
confidence: 80%
See 2 more Smart Citations
“…The mean 2-m temperature at 0800 LST is basically 3°C higher in T1 and T5 than in T2. As suggested in Grau et al (2020) based on high-resolution satellite observations, a higher environmental temperature tends to accompany a larger land-sea ΔT, which contributes to the establishment of sea breeze circulation. Here, it is difficult to use the global reanalysis data to directly resolve a realistic value of ΔT between the irrigated and arid areas.…”
Section: Synoptic Pattern Preference Of Boundaries and Their Associat...mentioning
confidence: 80%
“…To understand the synoptic pattern preference, the near‐surface temperature and ambient flow were investigated. These two factors have been widely recognized as playing the most fundamental role in determining sea/lake breeze occurrence (e.g., Atkins & Wakimoto, 1997; Biggs & Graves, 1962; Grau et al., 2020; Laird et al., 2001), but their impacts on vegetation‐contrast‐induced boundaries are less well documented.…”
Section: Environmental Features In Favorable Versus Unfavorable Synop...mentioning
confidence: 99%
See 1 more Smart Citation
“…The sea breeze develops as long as the thermal difference between sea temperature (SST, averaged sea surface temperature) and land temperature (LST, averaged land surface temperature) is maintained. Under sea-breeze conditions in the bay of Palma, Grau et al [24] found that the difference between LST and SST is greater than 5 • C during the central hours of the day.…”
Section: Formal Characteristics Of Sea Breezes In Mallorcamentioning
confidence: 99%
“…While numerous studies address SLBs (e.g., Simpson, 1996;Miller et al, 2003 and references therein;Nitis et al, 2005;Klaić et al, 2009;Babić et al, 2012;Jiménez et al, 2016;Grau et al, 2020) or LLBs over large lakes (e.g., Keen and Lyons, 1978;Arritt, 1987;Comer and McKendry, 1993;Laird et al, 2001;Sills et al, 2011;Gu et al, 2016), only a few authors have reported on LLBs produced by small lakes or reservoirs (Asefi-Najafabady et al, 2012;Giovannini et al, 2015). In terms of morphometry, small, medium, and large lakes correspond to maximum lake fetches (d) of d < 50 km, d ≈ 50-100 km, and d > 100 km, respectively (e.g., Crossman and Horel, 2010).…”
Section: Introductionmentioning
confidence: 99%